1988
DOI: 10.1159/000309867
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Argon Laser Retinal Buckling Performed in Myopic Subjects Presenting Rhegmatogenous Degenerations

Abstract: Twenty-two eyes of twenty-two patients suffering from retinal peripheral degenerations underwent preventive equatorial buckling with argon laser photocoagulation. The fellow eye was used as control. We evaluated the effects of laser photocoagulation on corneal sensitivity, on accommodation, on pupillary diameter and light reflex. In the postoperative period, up to the 3rd month, results were significant with respect to the control eye. The mechanisms to which the onset of these undesired alterations is due are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Posterior and peripheral argon PRP were then performed sequentially in the right eye. Both produced diminished responses to electrical stimulation and supersensitivity to pilocarpine early on, followed by essentially complete recovery (Fig 3, rows [9][10][11][12][13][14]. Similar findings were seen following PRP and HRMP in several other animals (48).…”
Section: Refraction and Accommodationsupporting
confidence: 63%
See 2 more Smart Citations
“…Posterior and peripheral argon PRP were then performed sequentially in the right eye. Both produced diminished responses to electrical stimulation and supersensitivity to pilocarpine early on, followed by essentially complete recovery (Fig 3, rows [9][10][11][12][13][14]. Similar findings were seen following PRP and HRMP in several other animals (48).…”
Section: Refraction and Accommodationsupporting
confidence: 63%
“…This niay be accompanied by paresis of the iris sphincter muscle, yielding a dilated pupil which reacts poorly to direct or consensual photic stimulation (9)(10)(11)(12). Similar occurrences may follow peripheral retinal photocoagulation (7,13) or cryotherapy (14) for myopic or lattice degeneration.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…It has been suggested that thermal injury to the parasympathetic motor nerves running in the short ciliary nerves anteriorly through the choroid and suprachoroidal space could explain this complication. 2,5,7,8 We have seen this in four cases following diode PRP with subTenon's local anaesthetic injection given as described by Stevens. 9 The cases are presented and the possible causes discussed.…”
Section: Introductionmentioning
confidence: 80%
“…Internal ophthalmoplegia has also been shown in myopic subjects after retinal equa torial buckling with argon laser photocoagula tion [7], Schiodte [4] related these effects partially to the use of retrobulbar anesthesia before each laser session.…”
Section: Discussionmentioning
confidence: 99%